2018
DOI: 10.1049/mnl.2018.5240
|View full text |Cite
|
Sign up to set email alerts
|

Indium tin oxide coated PET for differential pH‐sensing using field‐effect transistor based sensor

Abstract: Indium tin oxide (ITO) on polyethylene terephthalate (PET) substrate is characterised in terms of pH-sensitivity. Commercial ITO/PET sheet was cut in a shape of electrode and was connected to the gate-terminal of a metal-oxide-semiconductor field-effect transistor as the sensory part, creating an extended gate field-effect transistor (EGFET) pH-sensor. The quality of laser micromachining as well as the moulded ITO/ PET electrode is investigated. The pH-sensitivity and linearity of the sensor signal are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Recently, fabrication of EGFET on flexible substrates have been of interest for PoC applications. [ 294,317–322 ] Moreover, recently there has been an interesting development toward dual‐gated EGFETs, where the sensing electrode is connected to the gate electrode of a DG transistor, which amplifies the sensitivity of the device beyond the Nernstian limit due to capacitive coupling effect. [ 322–325 ]…”
Section: Fet‐based Microsensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, fabrication of EGFET on flexible substrates have been of interest for PoC applications. [ 294,317–322 ] Moreover, recently there has been an interesting development toward dual‐gated EGFETs, where the sensing electrode is connected to the gate electrode of a DG transistor, which amplifies the sensitivity of the device beyond the Nernstian limit due to capacitive coupling effect. [ 322–325 ]…”
Section: Fet‐based Microsensorsmentioning
confidence: 99%
“…Recently, fabrication of EGFET on flexible substrates have been of interest for PoC applications. [294,[317][318][319][320][321][322] Moreover, recently there has been an interesting development toward dual-gated EGFETs, where the sensing electrode is connected to the gate electrode of a DG transistor, which amplifies the sensitivity of the device beyond the Nernstian limit due to capacitive coupling effect. [322][323][324][325] Slewa et al reported a work in which they had synthesized 3D V 2 O 5 -doped with Sn, where Sn was prepared on porous silicon via solvothermal process, followed by annealing at 550 • C for 1 h. The sensing film characterization using XRD data showed that the crystal size and lattice expansion of Sn-doped V 2 O 5 had decreased.…”
Section: Egfet-sensing Film Materialsmentioning
confidence: 99%
“…Over the past decade, the sensing structure of extended-gate field-effect transistors (EGFETs) has been widely studied in related applications such as pH sensing and biomedical sensing. (1)(2)(3)(4) The EGFET structure offers several advantages, including low cost, simple packaging, insensitivity to temperature and light, flexibility in sensor head design, and improved long-term stability. (5) Many studies based on EGFET architecture use oxide-conductive materials as sensing materials, such as indium tin oxide (ITO) or indium zinc oxide (IZO).…”
Section: Introductionmentioning
confidence: 99%
“…glass and polyethylene terephthalate (PET)) along with its electrochemical properties, ITO has been widely applied by researchers as the sensory element of EGFETs for pH-sensing. 27,28 However, they could only show a reliable electrochemical behavior in the case of a hanging ITO electrode at stress-free condition operating next to a glass reference electrode. 27 A reliable ITO package with an integrated low volume cell is still missing.…”
mentioning
confidence: 99%
“…27,28 However, they could only show a reliable electrochemical behavior in the case of a hanging ITO electrode at stress-free condition operating next to a glass reference electrode. 27 A reliable ITO package with an integrated low volume cell is still missing. Furthermore, differential sensing and sensor miniaturization using ITO electrode have not yet been achieved.…”
mentioning
confidence: 99%